International human resource management : an environmental perspective. - Gronhaug, Kjell (1992)
Discusses human resource management in foreign subsidiaries of multinational companies. Outlines a model that can be applied by practioners to systematize their human resources planning by mapping environmental factors which may have substantial influence on the future operation of the subsidiary.